Organização e gerenciamento de conteúdos jornalísticos na web semântica - Marques, Iuri Lammel (2011)
Among the technologies that have modified the digital journalism since its inception, there are two that can be highlighted: 1) the World Wide Web (Web), a network of digital documents that has being used as a platform to the practice of journalism on the Internet and that determined the three generations of digital journalism; and 2) the databases aggregate to the Web, that have become the main technology behind the structuring of journalistic products in the transition between the third and fourth generation of digital journalism. In 2001, the scientist Tim Berners-Lee, inventor of the web, published a paper with a proposal of an extension to this network, which was called the Semantic Web. The paper proposed a change in the concept of the current web: from the traditional network made of documents to a network made of data, plus the technical ability to represent real concepts, such as people, places and objects. A great advantage of this proposal is that computers would be able to understand the data and identify their meanings. With a semantic network, the information could be organized and managed more efficiently and in an automated way, and the connections between the data would be richer than the current hyperlinks between documents. The concept of the Semantic Web is still maturing, but it is currently possible to find digital products that implement this concept. This research aims to analyze two real cases that apply the concept of the Semantic Web in digital journalism, specifically in the organization and management of the newspaper reports. For the theoretical background of research, we conducted a literature review on digital journalism, paradigm of the Digital Journalism on Databases (JDBD) and how the standard technologies of the Semantic Web work, such as RDF and ontologies. This is an exploratory research and it uses the case study as a method. The cases are the site 'World Cup 2010 BBC' and the site 'BBC Wildlife'. The analysis was performed using eight categories applicable to the study of JDBD. Among the results, it is found that the Semantic Web improve some of the characteristics of JDBD, mainly due to the automation on management tasks. Moreover, it identified that automated interoperability was the more advantageous benefit of Semantic Web to both digital journalism cases, and that it can become a potential rupture if the Semantic Web project come to succeed.